China's Quest for Energy Security - Downs, Erica Strecker (RAND Corporation, 2006)
China's two decades of rapid economic growth have fueled a demand for energy that has outstripped domestic sources of supply. China became a net oil importer in 1993, and the country's dependence on energy imports is expected to continue to grow over the next 20 years, when it is likely to import some 60 percent of its oil and at least 30 percent of its natural gas. China thus is having to abandon its traditional goal of energyself-sufficiency--brought about by a fear of strategic vulnerability--and look abroad for resources. This study looks at the measures that China is taking to achieve energy security and the motivations behind those measures. It considers China's investment in overseas oil exploration and development projects, interest in transnational oil pipelines, plans for a strategic petroleum reserve, expansion of refineries to process crude supplies from the Middle East, development of the natural gas industry, and gradual opening of onshore drilling areas to foreign oil companies. The author concludes that these activities are designed, in part, to reduce the vulnerability of China's energy supply to U.S. power. China's international oil and gas investments, however, are unlikely to bring China theenergy security it desires. China is likely to remain reliant on U.S. protection of the sea-lanes that bring the country most of its energy imports.